An investigation into the immediate effect of patellar taping on knee control in patients with adult acquired hemiplegia due to stroke - Dreyer, Sonette (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScPhysio (Physiotherapy))--University of Stellenbosch, 2009.